2019
DOI: 10.4274/tybd.galenos.2018.58561
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Stay in Intensive Care Unit: Retrospective Analysis of Predisposing Factors and Outcome

Abstract: ÖZ Amaç: Yoğun bakım ünitelerinde uzun yatış, maliyetin artması, kaynakların kullanılması, hasta mortalite ve morbiditesi ile sonuçlanan ciddi bir problemdir. Bu çalışmada yoğun bakım ünitesinde yatış süresinin uzamasına etki eden faktörlerin tartışılması amaçlandı. Gereç ve Yöntem: 2015-2017 yılları arasında 14 günden uzun yatan 219 hasta retrospektif olarak incelendi. Yaş, cinsiyet, yatış nedeni, yatış süresi, mekanik ventilasyon süresi, renal replasman tedavisi ihtiyacı, trakeotomi, kan transfüzyonu ihtiyac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
1
4
1
Order By: Relevance
“…According to the present study, the prevalence of prolonged ICU stays was 16.9% (95% CI = 13.5–20.5%), which indicated that one patient stayed longer than 14 days for every six patients admitted to the ICU. This finding aligns with several studies; for example, a study conducted in Barbados 25 , Taiwan 31 , Turkey 10 , 20 , and Thailand 32 ranged from 13.2 to 20.1%.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…According to the present study, the prevalence of prolonged ICU stays was 16.9% (95% CI = 13.5–20.5%), which indicated that one patient stayed longer than 14 days for every six patients admitted to the ICU. This finding aligns with several studies; for example, a study conducted in Barbados 25 , Taiwan 31 , Turkey 10 , 20 , and Thailand 32 ranged from 13.2 to 20.1%.…”
Section: Discussionsupporting
confidence: 92%
“…A pretested structured data retrieval form was developed from different related literatures 5 , 8 , 10 , 18 20 , 27 31 . It has five sections: sociodemographic characteristics, clinical characteristics, vital signs and laboratory investigations at admission, treatment given during the ICU stay, and patient outcomes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal failure, the use of vasopressor/inotropic, and mechanical ventilator are the most predictor found in previous studies. [22][23][24][25] APACHE IV seems to have less accuracy to predict PLOS in ICU despite the good discrimination and calibration in predicting mortality in our population. The AUC for predicting PLOS is 0.68 (0.62-0.74) and p value =0.01 for Hosmer-Lemeshow test for calibration, which considered poor.…”
Section: Plos Prediction Modelmentioning
confidence: 66%
“…In a study in Turkey, the need for renal replacement therapy and the use of inotropic, vasopressor agents were found to be predictive factors for prolonged ICU stay. 27 In a largescale study involving 16,018 patients from 13 countries in Europe, diuretic use was found to be one of the patient and care process factors with the highest impact on increased LOS hospital. 28 In the current study, it was seen that the need for inotropic agent support, diuretic agent use, and HD for prolonged ICU hospitalisation in AECOPD patients were significantly higher.…”
Section: Dal Et Al Analysed Prolonged Icu Hospitalisation Of 168mentioning
confidence: 99%